Buku dongeng Sunda sebagai literatur budaya pada buku Roesdi djeung Misnem - Evi Nursanti Rukmana; Kusnandar Kusnandar; Andri Yanto; Samson CMS; Elnovani Lusiana (Faculty of Communication, Padjadjaran University, 2022)
Sunda dialect is a local dialect from West Java Province that has to preserve. One of the learning materials can be conveyed through storytelling. Roesdi djeung Misnem book is a classic Sunda book that contains Sunda tales. Pabukon Ngadongeng Community Book Corner provides service for this book to material storytelling. This research aims to know the Sunda storytelling book as cultural literature to children in Roesdi djeung Misnem book at Pabukon Ngadongeng Community Book Corner through analysis of story meaning, kind of storytelling, characterization reader, and storytelling as a learning language. The research method used a qualitative approach through a narrative literature review. Roesdi djeung Misnem book has 19 tales with 13 themes from the meaning story: prudence, working together, smartness, gratitude, stinginess, loving, self-measurement, arrogance, brave, trust, honesty, good attitude, and glorifying parents. This kind of storytelling consists of tales with animal and human characters. Animal tales total seven tales, and human figures tales total 12 tales. In characterization reader, Roesdi djeung Misnem book can be read to children over nine. Sunda tales in this book can train to learn the Sunda language. So, librarians or Managers of Community Book Corner can design Sunda dialect learning materials through storytelling as an activity for local dialect revitalization.